Building Nationalism through Digital-Based Political Education - Nasution, Faiz Albar; Thamrin, Muhammad Husni; Kusmanto, Heri (Talenta Publisher, 2024)
This research discusses implementing digital-based political education and nationalism-building strategies for the younger generation in Indonesia's nation-building context. This research uses a descriptive qualitative method with a literature review approach. The study highlight the importance of political education as a vital instrument in strengthening political awareness and digital literacy in society. Challenges such as low political awareness and the spread of hoaxes affect the effectiveness of digital-based political education. The proposed strategies, such as curating relevant content, active participation in social media, online training, collaboration with figures and influencers, and civic projects, can help overcome these challenges. Periodic evaluations are needed to assess the effectiveness of strategies and tactics. By combining creative approaches in digital-based political education and focusing on building nationalistic character in the younger generation, this research shows great potential to increase political participation and strengthen national identity among the younger generation.